Practical COVID-19 Prevention Training for Obstetrics and Gynecology Residents Based on the Conceive–Design–Implement–Operate Framework - Wang, Xiaoxue; Zhou, Yangzi; Song, Zixuan; Wang, Yuting; Chen, Xueting; Zhang, Dandan (Frontiers in Public Health, 2022)
Background: The spread of COVID-19 poses a challenge for obstetrics and gynaecology (O&G) residents. In order to improve the theoretical knowledge and practical skills of residents in epidemic prevention and control, reduce work pressure and improve professional skills，effective and sound training models are required to improve the protection of O&G residents from COVID-19. Method: A total of 38 standardised training O&G residents working in Shengjing Hospital of China Medical University in March 2020 was selected. They were randomly divided into intervention and control groups. The control group underwent a protection theory exposition according to the traditional training method, while the intervention group adopted a conceive–design–implement–operate (CDIO) mode, arranged training courses in combination with the O&G specialty, and completed four modules of CDIO. After the training, the theoretical knowledge and practical operation were assessed, and the work stress and occupational identity scales were assessed. The assessment results and scores of the two groups of residents were analysed. Results: Compared with the scores of the residents in the control group, the theoretical and technical scores of the residents in the intervention group significantly improved (P < 0.05). In the evaluation of organisational management, workload, interpersonal relationship, and doctor–patient relationship pressure, the scores of the observation resident group were lower than those of the control group, with a statistical difference (P < 0.05). For the intervention group, the job stress and professional identity evaluation scores were significantly higher than those of the control group (P < 0.05). Conclusion: The CDIO model can effectively enhance the theoretical knowledge and practical skills of O&G residents in COVID-19 epidemic prevention protocols to reduce work pressure and improve professional identity. In addition, it provides new ideas, methods, and approaches for future clinical practice training.